Demand for Graduates – as a Criterion for Assessing the Quality of Educational Services and University Activities (Journal of Educational Sciences, 2020)
The article is devoted to the analysis of the demand for university graduates as an indicator of assessing the quality of educational services and university activities. The purpose of the article, based on a survey among students and interviews among employers, is to show factors that positively or negatively affect the demand for university graduates in the modern labor market through the prism of students and employers themselves. The main direction of the study is to show the main areas of partnership that affect the quality of educational services and the demand for graduates. The theoretical and methodological basis of scientific research are studies on the demand for university graduates in the modern labor market and the criteria for evaluating educational services. When writing the article, the methods of factor and sociological analysis are used. Actual data are collected through questionnaires among students and interviews among employers. The significance of this study lies in the identification of complex parameters for assessing the level of quality of educational services as one of the indicators of the demand for university graduates in the labor market. The results of the study in practical terms provide partnership methods between universities and employers in the formation of a specialist in a new format and provide aggregate indicators for determining the demand for university graduates.